Optimal Design and Simulation of a Microsuction Cup Integrated with a Valveless Piezoelectric Pump for Robotics. (27th June 2018) - Hu, Bingshan; Yu, Hongliu
Abstract : The traditional suction mechanism with an air pump in robotics is difficult to miniaturize. Integrating a piezoelectric pump into a suction cup is an effective method to achieve miniaturization. In this paper, a novel suction cup with a piezoelectric micropump is designed. The micropump is valveless and the suction cup is designed with a laminated structure in order to facilitate miniaturizing and manufacturing. A systematic optimization design method of the suction cup is introduced which addresses the static and dynamic driving characteristics of the piezoelectric actuator and the rectifying efficiency of diffuser/nozzle's optimization. The design is verified via simulation using an improved equivalent electric network model. Static lumped parameters in this model are calculated by the finite element method instead of the traditional analytic method, and the diffuser/nozzle's flow resistance is computed by integrating and introducing rectifying efficiency coefficient. Simulation results indicate that the suction cup can generate a stable negative pressure, and the equivalent electric network model can improve the simulation efficiency and accuracy. The maximum steady-state negative pressure of the suction cup can also be effectively improved after optimization.